PENERAPAN KONSEP WELFARE STATE DALAM MEMPRIORITASKAN PELAYANAN DIBIDANG BANTUAN HUKUM BAGI MASYARAKAT MISKIN DI RIAU - Libra, Robert; Fauzan, Muhammad (Esensi Hukum, 2023)
The concept of good governance in the preamble of the 1945 Constitution of the Republic of Indonesia as the foundation of the Republic of Indonesia's constitution can be seen in the preamble to the fourth paragraph which reads "Then from that to form an Indonesian State Government that protects the entire Indonesian nation and all of Indonesia's bloodshed and to promote general welfare, educate the nation's life. Legal aid activities are a government service in realizing a welfare state, the program must be evenly distributed and budget management must be prioritized for community welfare. In accordance with Article 23 (1) of the 1945 UUD NRI which states that the state revenue and expenditure budget as a manifestation of state financial management is determined annually by law and implemented openly and responsibly for the greatest prosperity of the people because the Legal Aid Program is closely related to the Economy of Poor Communities who need Legal Aid. The legal needs of the poor in Riau Province are numerous. therefore the writer is interested in analyzing it. The implementation of the Welfare State Concept in prioritizing services in the field of legal aid for the poor in Riau has not been maximized. The concept of a welfare state is the idea that the state is responsible for its citizens, namely by making its people prosperous through services, assistance, protection and prevention of social problems. Services in the field of legal aid in Riau are still constrained by equal distribution of services and budget priorities are also lacking.